S9 The role of ambulatory oxygen in improving the effectiveness of pulmonary rehabilitation for patient with chronic obstructive pulmonary disease – single blinded randomised trial. (12th November 2019) - Padmanaban, V; Collins, C; Lound, A; Lee, C; Mallia, P; Elkin, SL
Abstract : Background: Pulmonary rehabilitation (PR) is recognized as a core component of the management of patients with COPD. 1 Although the benefits of PR in COPD are well established, there remain a number of unanswered questions regarding how to maximise performance during PR, including the use of ambulatory oxygen. Studies investigating the effects of oxygen use during PR have had conflicting results. 2 Therefore, we aimed to investigate the effect of ambulatory oxygen on PR outcomes in COPD patients Methods: Patients with COPD referred to PR and have exercise desaturation (spo2<90%) during 6-minute walk distance (6MWD) test, and improve using ambulatory oxygen as per the British Thoracic Society Oxygen criteria, were randomised to receive either oxygen at the flow rate determined at the initial assessment to a maximum flow rate of 6lpm, or room air. Current oxygen users were excluded. 6MWD and chronic Respiratory questionnaire (CRQ) were measured pre and post completion of PR programme. The therapist who carried out the outcomes measure was blinded to the randomisation and was not involved in the delivery of PR Results: 20 patients (female-8) were recruited between April 2016- 2017, one patient withdrew after consent. There was no significant difference in the 6MWD and CRQ between the oxygen (n=9) and no oxygen group (n=10). In the oxygen group 56%, declined oxygen and 11% had no oxygen desaturation following PR. In the non-oxygen group, 40% declined oxygen and 20% had no exercise desaturation following PR. Conclusion: Use of ambulatory oxygen during PR, did not improve the 6MWD following completion of PR in COPD patients. Higher proportion of people in the oxygen group declined oxygen after completion of PR; this was mainly due to no perceived benefit with improving functional activity reported by patients. Also 16% of patients did not desaturate after completion of PR. This raises the question it may be better to assess patients for ambulatory oxygen following completion of PR. References: Pulmonary rehabilitation for COPD. McCarthy B, et al . Cochrane Reviews 2015 Ambulatory Oxygen for Exercise-Induced Desaturation and Dyspnea in COPD : Systematic Review and Meta-Analysis Ejiofor, et al . Journal of the COPD Foundation 2016.